2018
DOI: 10.3892/ol.2018.9590
|View full text |Cite
|
Sign up to set email alerts
|

Association and interaction between model for end‑stage liver disease score and minimally invasive treatment with regard to mortality of patients with hepatitis B virus‑associated hepatocellular carcinoma and portal vein tumor thrombi

Abstract: The development of minimally invasive treatment over the last two decades has had a great impact on hepatitis B virus (HBV)-associated primary liver cancer. The model for end-stage liver disease (MELD) score is the optimal evaluated parameter for mortality in patients with end-stage liver disease. However, the association between MELD score and minimally invasive treatment with regard to the mortality of patients with HBV-associated hepatocellular carcinoma (HCC) with a portal vein tumor thrombus (PVTT) remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The independent risk factors for 1-year OS in HBV-related HCC with high HBV-DNA levels were HGB level < 120 g/L, no-PR, PVTT, tumor size ≥ 5 cm, and tumor multiplicity. Known independent prognostic factors for death in HBV-related HCC include PVTT, tumor size, tumor number, HBV DNA, AST, and Child–Pugh score [ 38 , 39 ]. Previous studies have also demonstrated that patients with anemia have increased risk of death compared to those without anemia [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The independent risk factors for 1-year OS in HBV-related HCC with high HBV-DNA levels were HGB level < 120 g/L, no-PR, PVTT, tumor size ≥ 5 cm, and tumor multiplicity. Known independent prognostic factors for death in HBV-related HCC include PVTT, tumor size, tumor number, HBV DNA, AST, and Child–Pugh score [ 38 , 39 ]. Previous studies have also demonstrated that patients with anemia have increased risk of death compared to those without anemia [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%